ASSESSMENT AND UTILIZATION OF DIGITAL LIBRARY SERVICES IN THE NEW NORMAL: IMPLICATIONS TO STUDENTS’ ACADEMIC APPLICATION (Proceedings of the International Conference on Future of Education, 2023)
The digital library services of the library are of paramount importance to the college students’ academic activities. This study aimed to examine the students’ assessment and extent of utilization of digital library services in the new normal and its implications for students’ academic application. The study used a descriptive correlation design since it described the utilization and assessment of the digital library services and its influence in the academic applications of the students. A researcher-made questionnaire anchored on the factors of e-quality service of Ojasalo was the main instrument to gather data. A total of 310 students participated in the study. Multiple regression analysis was used to determine the influence of students utilization and assessment of the digital library services to their academic application. The findings reveal that the students’ utilization of digital library services is on an average of twice a week. The findings also reveal that students had a very good assessment of the quality of the digital library services. Furthermore, the students’ academic application of digital library services was described as being done to a "high extent". Additionally, the students’ utilization and assessment of digital library services significantly influences their academic application. The study concludes that quality of the digital library services has a significant predictor to students academic application. Thus, it is recommended to the librarians to continue improving the quality of the digital library services to increase its utilization among the students.
Keywords: Digital Library Services; Utilization; Academic Application; Quality Service